Etiological Factors of Acute Allergic Conditions in Children Living in the Conditions of the City of Bukhara (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The results of the research conducted among children living in the city of Bukhara showed that food allergens (68.2%) had a significant role in the structure of the causes of food allergies. Anamnestic intolerance to cow's milk was detected in 15.1%, egg protein in 12.5% of cases. The biggest cause of allergy was to an allergen from cow's milk. 1450 (15.1%) patients referred to this factor. Egg white was indicated in 1201 (12.5%) patients. 1037 (10.8%) patients pointed to beef meat. 950 (9.9%) patients indicated allergy to fish. Fruits and vegetables were considered the cause of allergy in 778 to 230 patients. It should be emphasized that the cause of the disease remained unexplained in 3053 patients, which is 31.8% of cases.